STUDENTS' CHALLENGES IN PRONOUNCING VOCABULARY AT SD IT ADNANI - Akbar Ibrahim; Asmaul Husna Lubis (Journal of Advances in Linguistics and English Teaching (JALET), 2025)
By employing a descriptive qualitative methodology that involves observations and interviews, this study investigates the difficulties that SD IT ADNANI primary school pupils have pronouncing language. The results demonstrated the range of pronunciation challenges that students encountered, most of which were caused by the phonetics of their home tongue, a deficiency in phonetic awareness, uneven practice, and restricted access to phonological resources. Further contributing factors to less practice  and slower progress were embarrassment and fear of making mistakes. Working together with teachers, parents, students, and the school community  is advised to address this problem. Phonetic education can be incorporated into the curriculum, frequent practice is encouraged, and a supportive learning environment can be established by schools to help students. A cooperative approach is crucial for pupils to overcome pronunciation difficulties and advance their language proficiency overall.